Biventricular endomyocardial biopsy in patients with suspected myocarditis: Feasibility, complication rate and additional diagnostic value. (1st March 2017) - Stiermaier, Thomas; Föhrenbach, Felix; Klingel, Karin; Kandolf, Reinhard; Boudriot, Enno; Sandri, Marcus; Linke, Axel; Rommel, Karl-Philipp; Desch, Steffen; Schuler, Gerhard; Thiele, Holger; Lurz, Philipp
Abstract: Background: Previous retrospective analyses have suggested that biventricular (BV) endomyocardial biopsy (EMB) is superior compared to selective left ventricular (LV) or right ventricular (RV) EMB. This study prospectively assessed the feasibility, safety and diagnostic performance of implementing a routine BV-EMB approach in patients with suspected myocarditis. Methods: Consecutive patients with clinically suspected myocarditis underwent EMB ( n  = 136). Myocarditis was defined as ≥ 14 infiltrating leukocytes/mm 2 in addition to enhanced human leukocyte antigen class II expression in professional antigen-presenting immune cells. The presence of viral genomes was assessed by nested (reverse transcriptase–) polymerase chain reaction. Results: BV-EMB was attempted in 132 patients (LV thrombus, n  = 3; complication during RV-EMB, n  = 1) and resulted in sufficient samples from both ventricles in 127 patients (96.2%). One major complication (pericardial tamponade requiring surgical revision) was observed during the 136 RV-EMB (0.7%). No severe complications occurred during the 132 LV procedures. Of the 127 patients with BV-EMB, myocarditis was diagnosed in 89 patients (70.1%). While 67 patients (75.3%) fulfilled the diagnostic criteria in both ventricles, the diagnosis of myocarditis was based on the results of LV-EMB only in 16 patients (18%) and of RV-EMB only in 6 patients (6.7%). Viral genomes were found in 45 of the 127 patients (35.4%) with evidence of virus genome only in the left ventricle in 10 patients (22.2%) and only in the right ventricle in 3 patients (6.7%). Conclusions: Implementing a routine BV-EMB approach is feasible and safe. In patients with suspected myocarditis, BV-EMB yields superior diagnostic performance compared to selective RV- or LV-EMB.